2021
DOI: 10.3389/fped.2021.661206
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Asthma and COVID-19: Protective Factors Against SARS-COV-2 in Pediatric Patients

Abstract: Coronavirus disease 2019 (COVID-19) is a pandemic infectious disease caused by severe acute respiratory syndrome coronavirus SARS-COV-2. Aberrant innate immunity response and cytokine storm are responsible for the syndrome. Apparently, in asthmatic patients, the inadequate antiviral immune response and the tendency for asthma exacerbation evoked by common respiratory viruses could explain increased susceptibility to SARS-COV-2 infection. However, asthma has not been suggested to be a risk factor in COVID-19 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 56 publications
2
18
0
2
Order By: Relevance
“…Children have a lower concentration of ACE2 receptors and a high eosinophil concentration, which that could further contribute to protection against a COVID-19 infection [21,23,30,35]. Sensitisation to allergens among asthmatic children appears to de-crease the number of ACE2 receptors present in the airway [16,28,42]. Glycoproteins in the mucus such as Muc5ac play a role in making more difficult to COVID-19 to arrive to the distal airway and to cause an infection [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children have a lower concentration of ACE2 receptors and a high eosinophil concentration, which that could further contribute to protection against a COVID-19 infection [21,23,30,35]. Sensitisation to allergens among asthmatic children appears to de-crease the number of ACE2 receptors present in the airway [16,28,42]. Glycoproteins in the mucus such as Muc5ac play a role in making more difficult to COVID-19 to arrive to the distal airway and to cause an infection [28].…”
Section: Discussionmentioning
confidence: 99%
“…Two studies show that constant exposure to allergens and the consequent allergic sensitisation of asthmatic children also decrease these receptors [16,28]. In one of the studies, it is noted that the production of mucus and glycoproteins such as Muc5ac could prevent SARS-CoV-2 from reaching the distal airway and causing pathology [28,42].…”
Section: Characteristics Of the Paediatric Asthmatic Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy, social distancing and facemasks have been proposed to reduce respiratory viral infection, leading to less hospital admission for asthma exacerbation in adults. Wearing facemasks has been proved to be protective against respiratory infections which are a common trigger of asthma exacerbation ( 39 ). Indeed, a large study in Hong Kong reported that the number of admissions for asthma exacerbation was reduced by 53.2% (95% CI 50.4–55.8%, p < 0.0001) in 2020 compared with past 5 years; admissions for asthma exacerbation decreased by 0.8% with every 1% increase in masking (95% CI 0.8–0.9%, p < 0.0001) ( 40 ).…”
Section: Decreased Physical Activity and Increased Sedentary Behaviors In Asthmatic Children And Its Impact During The Covid-19 Pandemicmentioning
confidence: 99%
“…So far, only indirect evidence is reported on expression of IL36 in SARS-CoV-2 infected patients ( 59 ). It should be also considered that IL36 is highly expressed in the lungs of allergic and asthma-affected patients, but studies have shown that asthma is not a risk factor in SARS-CoV-2-infected patients ( 60 ). Therefore, there is the possibility that IL36 inflammatory circuit contributes to protect patients with asthma against detrimental outcomes of SARS-CoV-2 infection.…”
Section: Ils and Their Involvement In Pathologies Where Ecs Play A Prominent Rolementioning
confidence: 99%